Crop Pest and Disease Remote Sensing Monitoring and Forecasting - Dong, Yingying; Geng, Yun; Guo, Anting; Huang, Wenjang; Ma, Huiqin; Ruan, Chao (Current Natural Sciences, 2022)
This book presents the research and applications carried out by the Vegetation Remote Sensing & Pest and Disease Application Research Team of Aerospace Information Research Institute of Chinese Academy of Sciences (AIR-CAS) in the field of pest and disease monitoring and forecasting during the past ten years. Organized in five parts, this work covers crop pest and disease remote sensing monitoring and forecasting mechanisms, algorithms, models, system development and applications. The first part introduces the importance and current research status of crop pest and disease monitoring and forecasting. From the second to the fourth parts, the authors engage readers with various subjects related to non-imaging and imaging remote sensing monitoring, remote sensing forecasting. The construction and application of crop pest and disease remote sensing monitoring and forecasting system are described in the last part. This book can be used as a reference book in the areas of agricultural information technology, 3S technology application, agricultural plant protection, agrometeorology and agricultural extension.Being internationally prestigious experts and young scientists, the authors provide an essential view of their important work supported by multiple major research funding programs (National Key R&D Program of China, Newton-UK-China Agri-centers, Strategic Priority Research Program of the Chinese Academy of Sciences, National Natural Science Foundation of China, Beijing Nova Program of Science and Technology, National special support program for high-level personnel, Ten-thousand TalentsProgram, Youth Innovation Promotion Association CAS, Hainan Provincial High level talent Program of Basic and Applied Basic Research Plan, etc.).